THE FACTORS AFFECTING EMPLOYEE RETENTION: A Case Study of Employee Training Development at ACLEDA Bank Plc. - Sovannara, Tuy; Sovang, Long; Bunteng, Long (Srawung: Journal of Social Sciences and Humanities, 2023)
Employee retention is a key success factor for organizations worldwide. Human resource management issues include curriculum development, employee capacity building, and lifelong learning. This manuscript proposes a conceptual framework for defining the relationship among curriculum development, employee capacity building, lifelong learning, career development, career success, and employee retention in the ACLEDA banking sector. Thus, this manuscript aims to determine the possibility of enhancing employee retention for employees in the banking sector in the ACLEDA bank sectors through curriculum development, employee capacity building, lifelong learning, career development, and career success opportunities granted to them by the organization. From this point of view, the service organization’s ability to retain talented employees and the low turnover rate can cause great inconvenience to the organization. The purposive sampling technique applies to collect data for this study. The research design for the current study is quantitative, with 453 participants. Item-Objective Congruence and Cronbach’s Alpha were employed to validate the constructs. Then, Confirmatory Factor Analysis (CFA) was used to verify convenient and discriminant validity and goodness of fit indices. The Structural Equation Modeling (SEM) was carried out to test the relationship among variables. The results of this paper examine the relationship among curriculum development, employee capacity building, lifelong learning, career development, and career success as critical factors affecting employee retention in the banking sector in Cambodia. The results of SEM indicated that curriculum development, employee capacity building, lifelong learning, career development, and career success as critical factors regarding the organization’s ability to retain its employees.